Perihilar cholangiocarcinoma masquerading as intrahepatic cholestasis of pregnancy: a case report and review of the literature - Xiao, Chao; Cao, Cheng-Jian; Xiao, Xue; Cheng, Qi-Jun (Frontiers in Medicine, 2024)
Cholangiocarcinoma (CCA) is a tumor arising from the epithelium of the intrahepatic bile ducts, rarely diagnosed before forty years old, and with a very aggressive trait: 95% of patients die within 5 years. We first report in great detail a perihilar CCA (pCCA) case during pregnancy that is masquerading as an ICP: first, she had typical pruritus, particularly in her limbs; second, a raised biomarker of total bile acid (TBA); third, onset in the second trimester fitting with epidemiology; and finally and importantly, there was no mass in her liver. First-line drugs were given to treat ICP, but finally failed, ultimately identified as pCCA. Following an inadequate excision, Chinese medicine was administered. After 26 months, she succumbed to cachexia. Because gestational symptoms are sometimes associated with pregnant disorders, pCCA in pregnant women is frequently misdiagnosed.The symptoms of jaundice, pruritus, and dilated bile duct in pregnant women may be alerts of pCCA.And, the appropriate treatment of pCCA of pregnancy could be surgery or chemotherapy; if surgery is not acceptable, chemotherapy could also extend the gestational week. Our work is meaningful and educational for the diagnosis and treatment of pregnant-relative diseases, like ICP and pCCA.